2022
DOI: 10.2196/31552
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology Among Persons With Memory Concerns and Their Caregivers in the United States During the COVID-19 Pandemic: Qualitative Study

Abstract: Background Stay-at-home orders and other public health measures designed to mitigate the spread of COVID-19 have increased isolation among persons with memory concerns (PWMCs: individuals diagnosed with cognitive impairment or Alzheimer disease or related dementias). The pandemic has also exacerbated challenges for family members who care for PWMCs. Although technology has demonstrated the potential to improve the social connections and mental health of PWMCs and their family caregivers (CGs), prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…In keeping with other studies, 36,44 our findings suggest that one important area to address is technology literacy for carers of people with dementia, and particularly those from an older generation who do not have the experience of using the devices or support from younger or more technologically knowledgeable family members. 44 Over recent years, resources have been developed to publicise the availability of digital devices and to upskill carers to use them as a means to support the independence, safety and well-being of people with dementia.…”
Section: Supporting Technological Inclusion For Carers Of People With...supporting
confidence: 88%
See 1 more Smart Citation
“…In keeping with other studies, 36,44 our findings suggest that one important area to address is technology literacy for carers of people with dementia, and particularly those from an older generation who do not have the experience of using the devices or support from younger or more technologically knowledgeable family members. 44 Over recent years, resources have been developed to publicise the availability of digital devices and to upskill carers to use them as a means to support the independence, safety and well-being of people with dementia.…”
Section: Supporting Technological Inclusion For Carers Of People With...supporting
confidence: 88%
“…Consequently, it is unknown whether the findings can be extrapolated to older people from more diverse backgrounds, and who may be less accustomed to these devices. Another study qualitatively examined the use of digital technologies by people with memory concerns and their predominantly co‐resident carers (90% of the sample) in the United States 36 . They found that carers used technology to remain socially connected, to reduce boredom by streaming music and films or attending online classes, and to enable periods of respite and independence through the use of Global Positioning System (GPS) technologies, which helped to ensure the person with dementia was safe whilst outside alone.…”
Section: Introductionmentioning
confidence: 99%
“…While still enabling caregivers to respond to emergencies involving the PWMC's health and safety, GPS technology occasionally gave caregivers a break. In the study, participant described how they tracked their wife's outdoor workouts without them by using GPS watch technology [31]. This finding is consistent with [18].…”
Section: Assistive Technologiessupporting
confidence: 82%
“…Studies have shown that family caregivers who were able to engage in more direct phone and email contact with relatives in long‐term care residences during the COVID‐19 lockdowns indicated greater emotional well‐being for themselves and their relatives, whereas relying on residential care staff to engage in communication resulted in lower perceived well‐being among family caregivers and their relatives 619 . Other studies suggested that some dementia family caregivers adjusted during the pandemic by relying more heavily on other sources of family/unpaid help as well as technologies to maintain social connection with relatives 620,621 . In a study of dementia caregivers of relatives living in nursing homes or similar residential settings, caregivers indicated a number of challenges during the COVID‐19 pandemic, including severely limited contact with relatives due to visitation restrictions, a lack of transparent information and communication from care residences, fears of relatives dying alone and concerns about overburdened staff at care residences 614 .…”
Section: Caregivingmentioning
confidence: 99%